Low-Dose Sodium Nitrite Fluid Resuscitation Prevents Lethality From Crush Syndrome by Improving Nitric Oxide Consumption and Preventing Myoglobin Cytotoxicity in Kidney in A Rat Model. Issue 1 (July 2017) - Murata, Isamu; Miyake, Yumi; Takahashi, Naomi; Suzuki, Ryuta; Fujiwara, Takayuki; Sato, Yuji; Inoue, Yutaka; Kobayashi, Jun; Kanamoto, Ikuo
ABSTRACT: Objective: Crush syndrome (CS) is a serious medical condition characterized by muscle cell damage resulting from pressure. CS has a high mortality, even when patients receive fluid therapy. We examined whether administration of NaNO2 -containing fluid can improve survival in a rat model of CS. Design: The CS model was generated by subjecting anesthetized rats to bilateral hind limb compression with a rubber tourniquet for 5 h. Rats were then randomly divided into six groups: sham; CS with no treatment; CS with normal saline treatment; CS with normal saline + 25 mEq/L bicarbonate treatment; and CS with normal saline + 200 or 500 μmol/kg NaNO2 . Measurements and Main Results: Blood and tissue samples were collected for histological and biochemical analyses at predetermined time points before and after reperfusion. Ischemic compression of rat hind limbs reduced nitrite content in the crushed muscle, and subsequent reperfusion resulted in reactive oxygen species-induced circulatory dysfunction and systemic inflammation. Rats treated with 200 μmol/kg NaNO2 showed increased nitric oxide (NO) levels, blood circulation, and neoangiogenesis, decreased generation of reactive oxygen species, and suppression of the inflammatory response, leading to complete recovery. Conclusions: Treatment with 200 μmol/kg NaNO2 prevents muscle damage induced by ischemia reperfusion via the protective effects of NO and suppression of systemic inflammation, thereby increasing survival rates in CS. Abstract : Supplemental Digital Content is available in the text